New Product Development Practices In Indonesia's Manufacturing Industry - Larso, Dwi (Jurnal Manajemen Teknologi, 2006)
New product development has been considered the key success factor for companies competing in today’s market. In this global economy, companies are striving for introducing better or really new products with faster deliveries and lower prices. Indonesia’s manufacturing industry is facing same challenges of tigh competition and the importance of new product development for success. This study Is intended to explore the practices of new product development in Indonesia’s manufacturing industry. Characteristic of interest include the type of new products developed, processes and organization of new product development, and the perceived performance of new products internally in the organization and externally in the market. The study focuses on Indonesia’s manufacturing industry. It was conducted through a survey using a questionnaire that has been used in previous studies. Data were received from various sizes of business consisting of 43% small, 36% medium, and 21 % large-size businesses. 5% of the businesses are owned by state/local government, 65% are private with full domestic ownership, and 30% are private companies owned partly by foreigners. Indonesia’s manufacturing industry is characterized by low level of new product introductions. Fiftly-three percent (53%) of the companies reported less than 4 new products per year. 21% of companies introduce between 5-14 new products per year. The industry focuses its new product development on more derivative products, not radical ones. Typically, the products are modifications of the current ones developed to respond to customer’s need. One-third of the company reported that their budget for R&D activities is 4% or less of the annual sales. The initiative to developed new products mostly comes form top management or from outside parties, not from within the organization. Although 61% of the companies reported that they have a formal procedure of new product development in place, mostly they do not have a separate unit taking care of new product development activities. 74% of the companies reportd that the NPD activities are conducted under other functional units, such as Marketing, R&D, or Production Department. The good news is observed that the companies reported high performance of new products launched. The new products launched were perceived as highly successful either internally in the organization or externally compared to its competitors in the market. The study shows that Indonesia’s manufacturing industry has high potential to being successful in introducing new products in the market. The industry should also focus on the development of platform and more radical products to ensure longer prosperity and create new markets. To achieve this, a separate unit in the organization dedicated to new product development is being proposed. Collaborations with other R&D institutions, such as universities and governmental institutions are possibilities to acquire more knowledge on basic and applied research. Keywords: new product development, R&D, Innovation, Manufacturing, Indonesia